Epidemiology of Peste des Petits Ruminants in Nigeria: A Review - Esonu, Daniel; Armson, Bryony; Babashani, Mohammed; Alafiatayo, Ruth; Ekiri, Abel B.; Cook, Alasdair J. C. (Frontiers in Veterinary Science, 2022)
Peste des petits ruminants (PPR) is a major constraint to the productivity of small ruminants in Nigeria. Understanding of the current epidemiological status of PPR is crucial to its effective control. A review of the epidemiology of PPR in Nigeria was performed and research gaps were identified. Thirty-seven eligible articles were reviewed: these presented information from 30 of the 36 states of Nigeria. Most studies focused on goats and/or sheep (n = 33) but camels (n = 4), cattle (n = 1) and wild ruminants (n = 2) were also considered. Fourteen (37.8%) of the articles reported seroprevalence in small ruminants, which varied from 0.0% to 77.5% where more than 10 animals were sampled. Molecular characterization and phylogenetic analysis were performed in 6 studies, with lineages II and IV, detected in sheep and goats. In one study in small ruminants, sequences clustering into lineage I showed a similarity to the vaccine strain, Nigeria 75/1, based on phylogenetic analysis of F gene sequences. However, if the preferred method of sequencing the N gene had been performed, this isolate would have been grouped into lineage II. According to N gene phylogenetic analysis in the other studies, sequences were identified that clustered with clade II-NigA, II-NigB (closely related to the Nigeria 75/1 vaccine strain), and others which were well separated, suggesting a high diversity of PPRV in Nigeria. Five articles reported the detection of lineage IV in 22/36 states, with IV-NigA and IV-NigB detected, highlighting its widespread distribution in Nigeria. Risk factors for PPRV seropositivity were reported in 10/37 (27.0%) articles, with a higher seroprevalence observed in female animals, although differing results were observed when considering species and age separately. There were inconsistencies in study design and data reporting between studies which precluded conduct of a meta-analysis. Nevertheless, several research gaps were identified including the need to investigate the low uptake of PPRV vaccine, and the economic benefits of PPR control measures to small ruminant farmers. Such data will inform PPR control strategies in Nigeria and subsequently contribute to the global 2030 PPR eradication strategy.